2017
DOI: 10.1038/s41562-017-0048
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience: When perceptual learning occurs

Abstract: A study now finds that visual perceptual learning of complex features occurs due to enhancement of later, decision-related stages of visual processing, rather than earlier, visual encoding stages. It is suggested that strengthening of the readout of sensory information between stages may be reinforced by an implicit reward learning mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Then, mean GFP per microstate was computed by averaging across the time points to which this microstate was assigned. As it takes 30 ms for a visual signal to reach the visual cortex (Sasaki and Watanabe, 2017), statistical analyses were restricted to microstates starting after 30 ms.…”
Section: Statistical Analyses Of Behavioral Datamentioning
confidence: 99%
“…Then, mean GFP per microstate was computed by averaging across the time points to which this microstate was assigned. As it takes 30 ms for a visual signal to reach the visual cortex (Sasaki and Watanabe, 2017), statistical analyses were restricted to microstates starting after 30 ms.…”
Section: Statistical Analyses Of Behavioral Datamentioning
confidence: 99%
“…There is evidence that training can also yield improvements of sensory perceptual abilities in both young and older people. It has been demonstrated that experience and training result in long-term visual perceptual learning (VPL; Sasaki and Watanabe, 2017). In this context, VR might turn out to be the ideal supporting platform for sensory perceptual training of complex stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Visual perceptual learning (VPL) is defined as long-term visual performance improvements after visual experiences, and is thought to reflect brain plasticity in adults 1 3 . However, the underlying neural mechanisms of VPL are not completely understood 4 . The brain area(s) that change in association with VPL remain hotly debated in the field.…”
Section: Introductionmentioning
confidence: 99%